A Survey of Social Capital Role in Urban Neighborhoods Regeneration (Case Study Islam Abad Karaj) - Abolfazl Meshkini; Mohammad reza Bahrami (تحقیقات کاربردی علوم جغرافیایی)
In the process of urban space creation, there exists a continuous exchange of ideas concerning the current state of that space and the desired conditions as articulated by its inhabitants. Improvements in the challenging realities of urban environments are often manifested through physical changes, one of which is urban regeneration. Given the proliferation of urban regeneration projects in recent decades, it is imperative to consider the social dimensions inherent in these initiatives. In this context, social capital, recognized as a significant social asset within neighborhoods, has assumed particular importance in the discourse surrounding regeneration. This research examines the role of social capital in the regeneration of urban neighborhoods, with a specific focus on the Islamabad Karaj neighborhood. The methodological approach employed in this investigation is descriptive-analytical. The primary objective of this study is to analyze the influence of social capital on the regeneration processes within the Islamabad Karaj neighborhood as perceived by its residents. Data collection for the theoretical framework was conducted using documentary analysis, while the empirical component involved a survey utilizing a questionnaire. The statistical population comprises individuals aged 15 years and older residing in a neighborhood of over 25,000 inhabitants, from which a sample of 410 respondents was selected through simple random sampling, employing Cochran's formula. For data analysis, Spearman's correlation coefficient and multiple linear regression analyses were conducted using SPSS software. The findings indicate a strong correlation between social capital and urban regeneration within the Karaj neighborhood of Islamabad. The implications of this research highlight the necessity to focus on the components of social capital and to implement policies aimed at its maintenance and enhancement to facilitate successful urban regeneration in the Islamabad Karaj neighborhood.